Media Competition Strategy in the View of Islamic Economy - Samawi, Mohammad Wirmon; Haryono, Slamet (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Press freedom at the end of the 20th century (after the 1999 reform) had an impact on increasing the number of mass media in Indonesia. Coupled with the presence of the internet as a new medium, it makes media competition more complex. Media companies need strategies to face competition and to survive. Facing this phenomenon, a number of media are starting to try to unite information, communication, and content technology which is known as media convergence. This research is qualitative research. Research data collection was carried out by means of observation, interviews, and documentation. This research concludes that Kedaulatan Rakyat implements the concept of media convergence. Media convergence is one of the developments in digital technology including mass media which involves many technological factors such as the integration of text, numbers, images, video, and sound. The presence of the internet encourages the mass media to apply the concept of media convergence such as online media, e-papers, e-books, streaming radio, and social media, combined with other media. Meanwhile, this article also uses the view of Islamic Economics which is based on the characteristics of the Prophet Muhammad, namely Shiddiq, Amanah, Fathanah, and Tabligh. It can be concluded that Kedaulatan Rakyat is in accordance with the teachings of Islamic Economics. combined with other media. Meanwhile, this article also uses the view of Islamic Economics which is based on the characteristics of the Prophet Muhammad, namely Shiddiq, Amanah, Fathanah, and Tabligh. It can be concluded that Kedaulatan Rakyat is in accordance with the teachings of Islamic Economics. combined with other media. Meanwhile, this article also uses the view of Islamic Economics which is based on the characteristics of the Prophet Muhammad, namely Shiddiq, Amanah, Fathanah, and Tabligh. And it can be concluded that Kedaulatan Rakyat is in accordance with the teachings of Islamic Economics.